PENGARUH KEPUTUSAN PEMBELIAN SEBAGAI IMPLIKASI DARI DIFERENSIASI PRODUK DAN CITRA MEREK HONDA CBI50R (Survey pada PT. Arimbi Amartapura Bandung) - Tirtamahya, Darmazakti Natajaya (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2017)
Competition in the motorcycle industry in Indonesia increasingly competitive, especially on sales of scooter type motorcycle. Honda CB150R launches motor to distinguish from other motorcycle is a motorcycle that is synonymous with motorcycles male. Of course Honda CB150R launch was intended to change the image of the motorcycle synonymous with women motorcycle motorcycles modified with an image identical motor gallant men. This study aims to determine the responses of respondents regarding product differentiation on Honda CB150R and brand image embedded in the minds of respondents GT Honda that influence purchase decisions on bike Honda CB150R. The population and sample of 70 respondents drawn from a visitor PT. Arimbi amartapura Motor through sampling techniques using slovin approach. Data were collected through questionnaires. The survey method used is descriptive and verification. Data analysis by the method of linear regression analysis using software SPSS for windows. Based on the survey results revealed that in partial product differentiation and brand image significant impact on purchasing decisions as well as the simultaneous differentiation of the product and brand image significant impact on purchasing decisions Honda CB150R on PT. Arimbi amartapura. Keywords: product differentiation, brand image, purchasing decisions